MATHEMATICAL ANALYSIS OF RECEPTORS FOR SURVIVAL PROTEINS - SHRUTI JAIN,; DURG SINGH CHAUHAN, (International Journal of Pharma and Bio Sciences, 2015)
In this paper, we have used the mathematical analysis to make a best linear model of the receptors of the survival proteins i.e. Epidermal growth factor (EGF) and Insulin using ten concentrations combinations. The model was made using different types of regression analysis in which regression coefficient (r2), adjusted regression coefficient (r2adj),PRESS, regression coefficient, cross validation (q2cv), Durban Watson statistics and other parameters was analyzed. We have plotted the probability density function (pdf) for normal distribution functions for the receptors i.e. epidermal growth factor receptor (EGFR) and insulin receptor (IRS) which is coming OK. We have also plotted the survival function and hazard function for normal distribution function using different methods(kalpan meier and herd johnson) for maximum likelihood and least square methods. Non parametric functions were also plotted.